RAM Holdings, RAM Ratings see top management changes - New Sarawak, Tribune (New Sarawak Tribune, 2011)
KUALA LUMPUR : RAM Holdings Berhad (RAM Holdings) has appointed Dato' Dr K Govindan as its Group Deputy Chief Executive Officer; he takes over from Wong Fook Wah, who has retired after more than 20 years with company.